The Extended Family of CD1d-Restricted NKT Cells: Sifting through a Mixed Bag of TCRs, Antigens, and Functions - Macho-Fernandez, Elodie; Brigl, Manfred (Frontiers in Immunology, 2015)
Natural killer T (NKT) cells comprise a family of specialized T cells that recognize lipid antigens presented by CD1d. Based on their T cell receptor (TCR) usage and antigen-specificities, CD1d-restricted NKT cells have been divided into two main subsets: type I NKT cells that use a canonical invariant TCR α-chain and recognize α-galactosylceramide (α-GalCer), and type II NKT cells that use a more diverse αβ TCR repertoire and do not recognize α-GalCer. In addition, α-GalCer-reactive NKT cells that use non-canonical αβ TCRs and CD1d-restricted T cells that use γδ or δ/αβ TCRs have recently been identified, revealing further diversity among CD1d-restricted T cells. Importantly, in addition to their distinct antigen specificities, functional differences are beginning to emerge between the different members of the CD1d-restricted T cell family. In this review, while using type I NKT cells as comparison, we will focus on type II NKT cells and the other non-invariant CD1d-restricted T cell subsets, and discuss our current understanding of the antigens they recognize, the formation of stimulatory CD1d/antigen complexes, the modes of TCR-mediated antigen recognition, and the mechanisms and consequences of their activation that underlie their function in antimicrobial responses, antitumor immunity, and autoimmunity.